Human Papillomavirus and Cancer Prevention: Gaps in Knowledge and Prospects for Research, Policy, and Advocacy - Franco, Eduardo L. (Vaccine, 2012)
The recognition that human papillomavirus (HPV) infection is the central, necessary cause of cervical cancer paved the way to new fronts of prevention via improved screening methods and HPV vaccination. Much has been learned in all fronts, from the molecular basis of our understanding of how HPV causes disease to the health economics of preventive strategies at the individual and population levels. Progress in other areas of cancer control has yet to show the same multi- and trans-disciplinary gains seen in research on HPV-associated malignancies, which is one of the unequivocal success stories in disease prevention. Yet, as an embarrassment of riches, much more research is needed to fill the gaps in knowledge that remain before we are able to reap the benefits from the knowledge translation from all fronts. Public health research on setting-specific implementation of HPV-based preventive strategies and more concerted advocacy to counter barriers facing the adoption of these strategies are likely to yield major dividends in reducing the burden of HPV-associated diseases.